(untitled) (Journal of Asian Development Studies, 2021)
The purpose of the study is examining the aspects which affects the dividend policy of normal and default sectors of Pakistan. The study population consists of all the companies fall in the normal and default sector for the year 2016. The panel data is used and gathered from the annual reports of selected listed companies of Pakistan including textile, banks, oil refinery etc. The panel data is analyzed by descriptive statistics, correlation and multiple regression techniques. The study tells us about the interrelationship of dependent and independent variables which are used in our analysis and to check how distinct variables and factors influence dividend payout ratio of any firm. The result shows us effect on dividend payout ratio in normal and default sectors of Pakistan, in which the values of non-default companies exceed the values of default companies based on the statistical results.